The effectiveness of e-booklet and animated story video on young women’s knowledge about herbal ingredients for vaginal discharge - Ratna Indah Kartika Sari; Dessy Hidayati Fajrin; Tessa Siswina; Aspia Lamana; Ayuningtyas Ayuningtyas (Universitas Aisyiyah Yogyakarta, 2025)
Adolescent girls are vulnerable to vaginal discharge (leukorrhea) due to hormonal changes and lack of understanding of reproductive health. Pathological leukorrhea often causes discomfort such as itching, unpleasant odor, and changes in the color of the discharge. According to WHO (2021), about 75% of women in Indonesia have experienced leukorrhea, and 45% have had it more than once. In West Kalimantan, the prevalence reaches 50%. Education using attractive media such as e-booklets and animated story videos can be an enjoyable and effective solution. This study aimed to determine the effectiveness of e-booklets and animated story videos in increasing adolescent girls' knowledge about herbal interventions for leukorrhea. This research employed a quasi-experimental design with a two-group pretest-posttest approach. Samples were selected using proportional random sampling, and data were collected through questionnaires. Data were analyzed using the Mann-Whitney test. The results showed a significant difference between the two groups (p = < 0,001 ), with a higher increase in knowledge among participants who received education through animated story videos compared to e-booklets. Conclusion: Animated story videos are more effective than e-booklets in increasing adolescent girls’ knowledge about herbal ingredients for managing leukorrhea.